PELATIHAN PEMANFAATAN DIGITAL MARKETING BAGI PELAKU UMKM KUE TRADISIONAL & MODERN - Nik Amah; Frisca Arvinda Prihandani; Juli Marwani (SURAKARTA ABDIMAS JOURNAL, 2023)
Abstract The aim of the training activity with the theme of using digital marketing in developing MSME marketing in Karangrejo village is to provide knowledge about digital marketing as well as training in the application of digital marketing. The methods used in this training are training, mentoring, and practice in using digital marketing. The stages of implementing this event include observation, interviews, training and evaluation. The material provided consists of an introduction to digital marketing, an explanation of digital marketing, an explanation of several problems that MSMEs often face when marketing so that sales turnover is stagnant, an explanation of several foreign terms related to digital marketing, then continued with practices related to digital marketing through the Canva application for photo/ video editing. products and create social media accounts. The impact of this training is that Legit Bali MSMEs can increase sales turnover because they have mastered how to carry out promotions through digital marketing in the form of publications on Instagram and Facebook, and can reach buyers from all regions. Keywords: MSMEs, Digital Marketing, Social Media, Canva